Effectiveness of mindfulness-based stress reduction on depression, anxiety, and stress of women with the early loss of pregnancy in southeast Iran: a randomized control trial - Masumeh Nasrollahi; Masumeh Ghazanfar Pour; Atefeh Ahmadi; Mogaddameh Mirzaee; Katayoun Alidousti (BMC, 2022)
Plain language summary Women who lose their pregnancies are more at risk than others for mental disorders such as anxiety, depression, and grief. Assessing stress, anxiety, and depression is critical to maintain women's overall health so that timely supportive interventions can be pursued if necessary. Eight MBSR intervention sessions were performed for 53 women with early pregnancy loss. The total intervention for all participants took 4 months. Results showed that the anxiety, depression, and stress of most participants decreased, which suggests that MBSR can be an effective non-pharmacological method to improve mental health.